Assessing the reliability of ecotoxicological studies: An overview of current needs and approaches. (30th January 2017) - Moermond, Caroline; Beasley, Amy; Breton, Roger; Junghans, Marion; Laskowski, Ryszard; Solomon, Keith; Zahner, Holly
ABSTRACT: In general, reliable studies are well designed and well performed, and enough details on study design and performance are reported to assess the study. For hazard and risk assessment in various legal frameworks, many different types of ecotoxicity studies need to be evaluated for reliability. These studies vary in study design, methodology, quality, and level of detail reported (e.g., reviews, peer‐reviewed research papers, or industry‐sponsored studies documented under Good Laboratory Practice [GLP] guidelines). Regulators have the responsibility to make sound and verifiable decisions and should evaluate each study for reliability in accordance with scientific principles regardless of whether they were conducted in accordance with GLP and/or standardized methods. Thus, a systematic and transparent approach is needed to evaluate studies for reliability. In this paper, 8 different methods for reliability assessment were compared using a number of attributes: categorical versus numerical scoring methods, use of exclusion and critical criteria, weighting of criteria, whether methods are tested with case studies, domain of applicability, bias toward GLP studies, incorporation of standard guidelines in the evaluation method, number of criteria used, type of criteria considered, and availability of guidance material. Finally, some considerations are given on how to choose a suitable method for assessing reliability of ecotoxicity studies. Integr Environ Assess Manag 2017;13:640–651. © 2016 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points: When evaluating the reliability of an ecotoxicity study or individual effect values from this study, a systematic and transparent assessment method is critical to ensure an unbiased and consistent categorization of reliability. Eight different methods for reliability assessment were compared using a number of attributes. Some additional considerations are given on how to choose a suitable method for assessing reliability of ecotoxicity studies.